Analisis Upaya Indonesia dalam Melawan Black Campaign Minyak Kelapa Sawit dari Uni Eropa - Riady, Caren; Badarul, Kholif; Hii, Helen (Proyeksi: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2023)
This article aims to explain Indonesia's efforts in combating the black campaign against palm oil from the European Union. Globalization is an era that encourages every sector to be interconnected with one another. Of course, this phenomenon also encourages the rapid development of certain sectors such as international trade. As a response to this situation, Indonesia, which has potential in its natural resources, taking advantage of this opportunity to become one of the main exporters of palm oil in the world. However, the issue of environmental damage and human rights violations had become the main obstacle that prompted the European Union to take firm steps to follow up on this issue. Although there have been concrete steps from the palm oil industry to create a system that is more sustainable than before, the impact has been quite influential on the share of Indonesian CPO in the European market. Therefore, this paper will explore more deeply about Indonesia's efforts to fight these stereotypes. The data collection technique is in the form of a literature study method, which is to examine several literary works such as books, journals, and articles that are considered relevant to the research topic both found online and offline. From the results found to date, Indonesia has made a series of concrete efforts ranging from policies, and diplomacy, to legal actions.